2021
DOI: 10.3847/2041-8213/ac0727
|View full text |Cite
|
Sign up to set email alerts
|

Thermal History of Asteroid Parent Bodies Is Reflected in Their Metalorganic Chemistry

Abstract: Organo-magnesium compounds were shown to contribute significantly to the soluble carbon molecular complexity and diversity of meteorites, and their analysis increases our knowledge on carbon stabilization/sequestration processes in the asteroidal parent body. Here we present a new group of sulfur-magnesium-carboxylates detected using ultra–high-resolution mass spectrometry in a variety of meteorites. These novel compounds show increased abundance correlated with the thermal history of the asteroid parent bodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Organomagnesium compounds (CHOMg) have been shown to be markers of shock/heating history in the parent body (Ruf etal., 2017, Bischoff et al, 2019b (Fig. S6); Kerraouch et al, 2019, Matzka et al, 2021. High pressure and temperature events generally lead to a higher number of CHOMg and CHOSMg compounds together with a loss in chemical diversity, especially of nitrogen and sulfur compounds (Langbroek et al, 2019).…”
Section: Organic Matter and Heating Processmentioning
confidence: 98%
“…Organomagnesium compounds (CHOMg) have been shown to be markers of shock/heating history in the parent body (Ruf etal., 2017, Bischoff et al, 2019b (Fig. S6); Kerraouch et al, 2019, Matzka et al, 2021. High pressure and temperature events generally lead to a higher number of CHOMg and CHOSMg compounds together with a loss in chemical diversity, especially of nitrogen and sulfur compounds (Langbroek et al, 2019).…”
Section: Organic Matter and Heating Processmentioning
confidence: 98%
“…In addition, the abundance and structural diversity of high-pressure chemical markers dihydroxymagnesium carboxylates [RCO 2 Mg(OH) 2 ] (CHOMg) progressively increased with shock metamorphism ( 31 ). Similarly, sulfur-bearing organomagnesium compounds [RCO 2 Mg(OH) 2 SO 2 ] (CHOSMg) were described as thermal-stress chemical witnesses in meteorites, enabling tracking of peak temperatures or long-duration thermal effects ( 34 ). The close relationships between respective CHO and CHO(S)Mg chemical spaces are thus dependent on pressure and temperature conditions and indicative of a coevolution of organic molecules and colocalized minerals in Mars rocks as well.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, there have been several reports of metal-organic compounds in meteoritic organic matter that have implications for understanding parent-body interactions with origins of life implications [141][142][143]. A study by Ruf and colleagues surveyed 61 meteorites over a wide range of petrologic types.…”
Section: Organometallic Systems Related To Chiralitymentioning
confidence: 99%
“…Another study looked at the soluble organic fraction of 44 meteorites and found a novel homologous series of sulfur magnesium carboxylates. They appear to be thermally stable and their abundance was correlated with increasing thermal maturity [143]. Smith and colleagues looked at the origin of cyanide in the CM2 Murchison meteorite and found that it was primarily bound (and subsequently released) as iron cyanocarbonyl ([Fe II (CN) 5 (CO)] 3− and [Fe II (CN) 4 (CO) 2 ] 2− ) organometallic complexes.…”
Section: Organometallic Systems Related To Chiralitymentioning
confidence: 99%
See 1 more Smart Citation